Nonequilibrium molecular dynamics - Hoover, Wm.G.; Hoover, C.G. (Condensed Matter Physics, 2005)
Nonequilibrium Molecular Dynamics is a powerful simulation tool. Like its equilibrium cousin, nonequilibrium molecular dynamics is based on timereversible equations of motion. But unlike conventional mechanics, nonequilibrium molecular dynamics provides a consistent microscopic basis for the irreversible macroscopic Second Law of Thermodynamics. We recall here how fast computers led to the development of nonequilibrium molecular dynamics from the statistical mechanics of the 1950s. Computer-based theories facilitated revolutionary breakthroughs in understanding during the 1970s and 1980s. The new idea key to the nonequilibrium development was the replacement of the external thermodynamic environment by internal control variables. The new variables can control temperature, or pressure, or energy, or stress, or heat flux. These thermostat, barostat, ergostat, ... variables can control and maintain nonequilibrium states. We illustrate the methods with a simple example well-suited to student exploration, a thermostatted harmonic oscillator exposed to a temperature gradient.